PROSPECTIVE COMPARISON OF ARNI [ANGIOTENSIN RECEPTOR-NEPRILYSIN INHIBITOR] WITH ACEI [ANGIOTENSIN CONVERTING-ENZYME INHIBITOR] TO DETERMINE IMPACT ON GLOBAL MORTALITY AND MORBIDITY IN HEART FAILURE TRIAL (Неотложная медицинская помощь)
Источник: McMurray J.J., Packer M., Desai A.S., et al. Angiotensin-Neprilysin Inhibition versus Enalapril in Heart Failure. N. Engl. J. Med. – 2014. – Vol. 371. – P. 993–1004.